Congruency Analyses in Agricultural Organizations - Tóth, Anikó (Acta Agraria Debreceniensis, 2006)
Management is one of the ancient activities. Managerial behaviour helped humans to become sociable creatures. The aims and roles of management have continually changed along with social and economic changes. Some management theories in the early literature interpret the managerial function as „to instruct” and „to control” subordinates. The manager – having the appropriate authority – unilaterally appoints the expected activities in accordance with the objectives of the organization and his/her own wish. Its form is the instruction or the command. Later, organizations and management theories defined the managerial function rather as the impact on the employees than (or instead of) a unilateral manifestation of will. These focus on collaboration and imitation instead of on obedience. These theories were based on the fact that the employees work hard to succeed in meeting organizational goals because they want to meet their own needs, desires and wishes. Today, management means being in a relationship with colleagues, effective and successful working methods and, last but not least, commitment and liability for the company. The responsibilities of directors are to estimate the employees’ competences and to apply the workforce expediently. In our opinion, the two most important questions of human resource management (HRM) will be: • the expectations made of the manager by the subordinates, • the expectations made of the subordinates by the manager. The expectations of management have continuously evolved along with the social, political and economical improvement. We consider the most important requirements will be the following: • the exploitation of employees’ abilities (especially the leaders’), • the exploitation of human resource, • aim-oriented leadership related to different management levels. The actual research covers only the examination of managerial requirements. We experienced that the expectations are affected by many factors starting with the fulfillment of a specific task to the social environment as a whole. Managements of the last century did not require such self-reliance, creativity and broad knowledge from their subordinates as they do today. Employees have to be able to adapt to new tasks, technology and methods; have to react quickly against the problems; and be loyal to the company and the manager. We plan to expand our research backwards as well, in which we will search for the answer what kind of expectations are formulated by subordinates on the manager. Thus, we can approach and reveal the expectations (the examined factors) from two sides. Due to this method, we would like to work out such coherences which can help us to demonstrate the opinions of the differently qualified employees of the organisations. The applied method provides us facilities to carry it out in various organisational parameters, such as functional form, size, effectiveness, range of activity.